EXPLORING THE ROLE OF ENVIRONMENTAL ACCOUNTING IN PROMOTING CORPORATE SUSTAINABILITY PRACTICES - Fatmasari, Raden Roro; Padma Hanuun, Nazhira Nindya; Yolistina, Anggun (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background The growing global awareness of environmental issues, such as climate change, resource depletion, and pollution, has led to increased pressure on corporations to adopt sustainable practices. Environmental accounting has emerged as a key tool for integrating environmental concerns into business operations. It involves identifying, measuring, and communicating environmental costs and benefits, enabling organizations to assess their environmental impact and make more informed decisions. Research Method This research employs a mixed-methods approach, combining both qualitative and quantitative data to examine the role of environmental accounting in promoting corporate sustainability. The study involves a comprehensive literature review, case studies, and surveys conducted among 50 corporations across various sectors, including manufacturing, energy, and services. Results and Conclusion The findings of this study demonstrate that environmental accounting plays a crucial role in enhancing transparency, improving resource efficiency, and fostering stakeholder engagement. The research reveals that companies that adopt environmental accounting practices are better able to track and report their environmental performance, leading to increased trust among stakeholders and improved relationships with customers, investors, and local communities. Moreover, environmental accounting enables companies to optimize resource usage, reduce waste, and lower operational costs, contributing to both environmental and financial sustainability. Contribution This study contributes to the existing body of knowledge on environmental accounting by providing a comprehensive analysis of its role in promoting corporate sustainability practices. It offers valuable insights into the benefits and challenges of adopting environmental accounting and provides practical recommendations for overcoming the barriers to its implementation. The study also highlights the importance of transparency, stakeholder engagement, and resource efficiency in achieving sustainability goals and demonstrates how environmental accounting can help companies align their operations with societal expectations.